GENDER REPRESENTATION IN MALAYSIAN SECONDARY SCHOOL ENGLISH LANGUAGE TEXTBOOKS - Jayakaran Mukundan; Vahid Nimehchisal (Indonesian JELT, 2008)
This study was conducted to describe the representation of gender in Forms 1, 2, 3, and 4 English language textbooks in Malaysian secondary schools. Gender-biased materials have been reported to affect the motivation of students who go through the textbooks (Treichler and Frank, 1989). Computer analysis tools and manual analysis were used to perform content and linguistic analyses. These methods in addition to discourse analysis of the text books aided the researchers to disclose the predictable patterns of sexism in the textbooks in order to identify the existence and extent of stereotypes. The results clearly indicate there is an absolute gender bias with males outnumbering females. Further, certain nouns referring to males precede those referring to females; however, males almost exclusively turn out to represent negative characters. Keywords:   Gender; English language textbooks; Content analysis; Corpus based analysis;  Stereo-typed roles